STAKEHOLDERS PERCEPTIONS ON FACTORS INFLUENCING CORPORATE GOVERNANCE IN A SOUTH AFRICAN LOCAL GOVERNMENT MUNICIPALITY - Emanuel Ramatsoma , Phetole; Mazhazha-Nyandoro, Zivanayi (The journal of contemporary issues in business and government, 2023)
Despite the promulgation of corporate governance frameworks there is an increase in the number of municipalities receiving unqualified audits indicating failures in corporate governance and poor service delivery in South Africa. The study comprises one-hundred and twenty (120) respondents drawn from municipalities’ internal and external stakeholders. Data collection used semi-structured interviews and self-completion questionnaires. The main findings on factors influencing corporate governance include dysfunctional organisational cultures, ineffective human resource management systems, dearth of managerial skills, poor organisational communication, political interference, cadre deployment, corruption, and fraud. The study conclusions are that the non-enforcement of mandated corporate governance provisions by the respective government structures compounded by political interference and deployment of unqualified cadres account for failures in corporate governance systems and the subsequent poor service delivery in the municipality. The recommendations include the need for the national government to enforce compliance with established corporate governance processes and implement consequence management policies across-the-board. Further to the need for reviewing the merits of the cadre deployment policy and addressing the political interference in municipal operations.